Surfaces away from horizons are not thermodynamic - Zhi-Wei Wang (Nature Portfolio, 2018)
It has been conjectured that gravity may emerge from an entropic force arising on a holographic screen due to its purportedly intrinsic thermodynamic properties. Here, the authors test this conjecture by demonstrating that this key assumption of entropic force is inconsistent with general relativity.